Analisis Konflik Kerja dan Komunikasi Kerja Terhadap Kinerja Karyawan PT. Gersindo Minang Platantion - Sumeba, Stevany; Sunreni, Sunreni (Fakultas Ekonomi, Universitas Ekasaktii, 2023)
The purpose of this study was to determine: The partial effect of work conflict on employee performance. The influence of communication partially on employee performance. The effect of work conflict and communication simultaneously on the performance of employees of PT. Gersindo Minang plantation. The population of this research is the employees of PT. Gersindo Minang Platantion with a total of 618 people and a sample obtained through calculations using the slovin formula as many as 242 people. The sampling technique of this study used the accidental sampling technique. The research data used primary data which was collected through distributing questionnaires to employees. The data analysis method in this study uses multiple linear regression analysis, coefficient of determination and hypothesis testing t and F. The results of the analysis show that Work conflict partially has a negative and significant effect on employee performance. Work communication partially positive and significant effect on employee performance. Work conflict and communication simultaneously have a positive and significant effect on employee performance. The contribution of work conflict and communication to employee performance is 25.1% while the remaining 75.9% is influenced by other variables outside of this study.